A Review on the Emerging Asian Aquaculture Fish, the MalaysianMahseer (Tor tambroides): Current Status and the Way Forward - Chung, Hung Hui; Mei, Melinda Lin Lau; Whye, Leonard Kit Lim; Sairatul Dahlianis, Ishak; Ambok Bolong, Abol-Munaf (Springer, 2021)
The Malaysian mahseer (Tor tambroides)is a sport, ornamental and food all-in-one treasured aquaculture fish member of the Cyprinidae family. However, this freshwater riverine species is currently under the threats of habitat degradation and overfishing, apart from its poorly documented taxonomy. Despite its socio-economic significance, taxonomy confusion and conservation inadequacy, the knowledge gaps in some fields like the genomic landscape and biology are yet to be filled. In this comprehensive review, we presented an overview of all the past and current T. tambroides related research fields, namely morphology, population genetics, growth environment, reproduction, diet and nutrition, metagenome, mitogenome as well as conservation. Furthermore, we have included some future perspectives and recommendations for the advancement of the respective fields. It is anticipated that this review would be of great benefit to those planning to consolidate resources and work in tandem to pace the conservation and fish farming industry improvement endeavours.